The Relationship Between Plasma Concentrations of Lutein and Zeaxanthin with Self-Reported and Actual Prevalence of AMD in an Irish Population-Based Sample. (4th March 2018) - Moran, Rachel; Beatty, Stephen; Stack, Jim; O'Halloran, Aisling M.; Feeney, Joanne; Akuffo, Kwadwo O.; Peto, Tunde; Kenny, Rose Anne; Nolan, John M.
ABSTRACT: Purpose : To investigate plasma lutein (L) and zeaxanthin (Z) concentrations with grading-confirmed and self-reported prevalence of age-related macular degeneration (AMD). Material and methods : Data collected from a nationally representative prospective cohort study of community-dwelling adults aged 50 years and over in the Republic of Ireland. Participants underwent a computer-assisted personal interview and a center-based health assessment. Plasma concentrations of L and total Z (Z and meso -zeaxanthin [MZ]) were measured by high performance liquid chromatography, and retinal photographs were graded using a version of the AMD International Classification and Grading System. Consumption of supplements containing L and/or Z and/or MZ was recorded as supplement use. Four groups were identified: Group 1 ( n = 24): AMD-afflicted and correctly aware; Group 2 ( n = 264): AMD-afflicted but unaware; Group 3 ( n = 41): AMD-free and incorrectly believed that they were afflicted with the condition; Group 4 ( n = 4094): AMD-free and correctly self-reported absence of AMD. Results : Of 4, 423 participants with plasma concentrations of L and Z and gradable retinal photographs, 288 (6.5%) were afflicted with AMD, and 65 (1.5%) self-reported AMD. Controlling for family history and age, the relationship between grading-confirmed AMD and plasma L was positive and significant ( p < 0.001). Mean plasma concentrations of L in Group 2 (mean = 0.2162 ± 0.132 µmol) and Group 4 (mean = 0.2040 ± 0.121 µmol/L) were significantly lower than Group 1 (mean = 0.4691 ± 0.0.372 µmol/L) and Group 3 (mean = 0.3176 ± 0.0.235 µmol/L). Supplement use was reported by 41.7% and 17.1% of participants in Groups 1 and 3, respectively, but only 2.7% and 1.9% of participants in Groups 2 and 4, respectively. Conclusion : A belief that one suffers from AMD, whether justified or not, is associated with supplement use and with higher plasma concentrations of L.